1968
DOI: 10.1085/jgp.51.5.589
|View full text |Cite
|
Sign up to set email alerts
|

The Site of the Stimulatory Action of Vasopressin on Sodium Transport in Toad Bladder

Abstract: Vasopressin increases the net transport of sodium across the isolated urinary bladder of the toad by increasing the mobility of sodium ion within the tissue. This change is reflected in a decreased De resistance of the bladder; identification of the permeability barrier which is affected localizes the site of action of vasopressin on sodium transport. Cells of the epithelial layer were impaled from the mucosal side with glass micropipettes while current pulses were passed through the bladder. The resulting vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
47
0

Year Published

1971
1971
1993
1993

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 12 publications
8
47
0
Order By: Relevance
“…Studies of the site of action of the hormone on sodium transport, on the other hand, have not been so definitive. It has been thought that the hormone affects the mucosal barrier to sodium Frazier and Hammer, 1963;Civan and Frazier, 1968), and the present work offers direct confirmation of this. As shown in Table I, there is, on the average, a 77% increase in the influx of sodium from the mucosal chamber into the transport pool.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Studies of the site of action of the hormone on sodium transport, on the other hand, have not been so definitive. It has been thought that the hormone affects the mucosal barrier to sodium Frazier and Hammer, 1963;Civan and Frazier, 1968), and the present work offers direct confirmation of this. As shown in Table I, there is, on the average, a 77% increase in the influx of sodium from the mucosal chamber into the transport pool.…”
Section: Discussionsupporting
confidence: 81%
“…Frazier (1962) has shown that there is a small electronegative well within the cells in the short-circuited toad bladder. Although the electrical potential profile is not known during short circuit following the addition of vasopressin, Civan and Frazier (1968) have shown that under open-circuit conditions there is little or no change in the potential across the mucosal barrier following the addition of the hormone. We can therefore postulate that however vasopressin acts to enhance entry of sodium, it does so without initially altering the electrochemical potential gradient for this ion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curran, Herrera & Flanigan (1963) later developed a kinetic technique for the evaluation of the rate coefficient for 24Na movement across the individual barriers of the Na-transporting compartment, and demonstrated that ADH does in fact increase the Na permeability of the outer barrier. This conclusion can also be reached on the basis of the study of Na movement across urinary bladder (Leaf & Dempsey, 1960;Bastide & Jard, 1968) and is supported by the measurement of electrical parameters (Civan & Frazier, 1968). Yet the conclusion that ADH increases the flux of Na across the outer barrier does not rest on the direct measurement of this flux.…”
mentioning
confidence: 73%
“…As discussed below, the entrance of Na into the epithelium across the outer barrier has always been regarded as a rate limiting step in the overall process of Na transport across epithelial membranes (Civan & Frazier, 1968;Curran & Gill, 1962;Curran et al 1963;Frazier, Dempsey & Leaf, 1962). Comparison of control data in Tables 1 and 2, though, indicates that JOT is larger than the transepithelial influx under all comparable conditions tested.…”
Section: Na Influxmentioning
confidence: 99%